2018
DOI: 10.1007/s00204-018-2311-z
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary trends in toxicological research on arsenic

Abstract: There is a plethora of recent publications on all aspects relevant to the toxicology of arsenic (As). Over centuries exposures to arsenic continue to be a major public health problem in many countries. In particular, the occurrence of high As concentrations in groundwater of Southeast Asia receives now much attention. Therefore, arsenic is a high-priority matter for toxicological research. Key exposure to As are (traditional) medicines, combustion of As-rich coal, presence of As in groundwater, and pollution d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…In a study by Pereira et al, Swiss albino mice were exposed to 10 µg arsenic trioxide/g body weight through oral route and 5 µg arsenic trioxide/g body weight through intraperitoneally for a duration of 30 days, it was found that there was altered hemogram values in the peripheral blood that reflected the altered hematopoiesis that was next evident by reduced bone marrow cellularity and deviated bone marrow cell morphology that was observed by scanning electron microscopy. The stromal cells were not able to maintain a healthy matrix [62].…”
Section: Toxicity Related To Hematopoietic Systemmentioning
confidence: 95%
“…In a study by Pereira et al, Swiss albino mice were exposed to 10 µg arsenic trioxide/g body weight through oral route and 5 µg arsenic trioxide/g body weight through intraperitoneally for a duration of 30 days, it was found that there was altered hemogram values in the peripheral blood that reflected the altered hematopoiesis that was next evident by reduced bone marrow cellularity and deviated bone marrow cell morphology that was observed by scanning electron microscopy. The stromal cells were not able to maintain a healthy matrix [62].…”
Section: Toxicity Related To Hematopoietic Systemmentioning
confidence: 95%
“…Arsenic compounds were among the first substances used to control agricultural pests (Bolt 2013). Significant concentrations of arsenic occur naturally in the environment, usually in conjunction with metals such as cobalt, nickel, iron, lead and copper (Chou and De Rosa 2003).…”
Section: Arsenicmentioning
confidence: 99%